2009
DOI: 10.1177/1553350609335035
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Cancellations on the Day of Surgery at Two Major University Hospitals

Abstract: Cancellations of elective cases on the day of surgery waste valuable operating-room time. The authors studied cancellations at an American hospital and a Norwegian university hospital to test (a) whether the quality of hospital administrative data on cancellations is sufficient for meaningful comparative analysis and (b) whether causes of cancellations at these 2 major academic hospitals are comparable. Large retrospective cause-of-cancellation data sets were obtained from each hospital. The authors then prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 7 publications
1
39
0
1
Order By: Relevance
“…Studies at teaching hospitals in other countries, such as the United States and Norway, have reported that unfavorable clinical condi ons for surgery and lack of beds are major contribu ng factors, rather than absenteeism (15) . In a study evalua ng the cancella on of pediatric surgeries, the informa on provided to the mothers and/or rela ves was incomplete and superfi cial, which led to doubts and gaps in communica on and caused feelings of anxiety, fear, insecurity and anguish.…”
Section: Discussionmentioning
confidence: 99%
“…Studies at teaching hospitals in other countries, such as the United States and Norway, have reported that unfavorable clinical condi ons for surgery and lack of beds are major contribu ng factors, rather than absenteeism (15) . In a study evalua ng the cancella on of pediatric surgeries, the informa on provided to the mothers and/or rela ves was incomplete and superfi cial, which led to doubts and gaps in communica on and caused feelings of anxiety, fear, insecurity and anguish.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis was that this system would increase the number of case reviews and the number of SBP and PBLI learning opportunities. This represents part of our ongoing efforts to ensure the highest quality education possible through innovative technological methods [6] and a new application of information systems in our ongoing efforts to track and compare causes of day-of-surgery cancellations [19].…”
Section: Introductionmentioning
confidence: 99%
“…Cancellation reasons also vary across studies including medical condition changes, patient no show, and scheduling issues. Importantly, most of these studies are retrospective, which does not permit accurate assessment of time sensitive factors which might cause some inaccurate explanation of the cancellation; and the outcomes might have selection bias [2,5,8].…”
Section: Introductionmentioning
confidence: 99%